Comparative Anatomy of Mandibular Neurovascular Canals in Modern Human and Great Apes: A Pilot Study with Cone Beam Computed to Mography - Corpas, Livia; Huang, Yan; Mowafey, Bassant; Semal, Patrick; Liang, Xin; Lambrichts, Ivo; Politis, Constantinus; Jacobs, Reinhilde (International Journal of Human Anatomy, 2018)
The aim of the present study was to compare mandibular neurovascular canal anatomy in human and great apes by using cone beam computed tomography (CBCT). The anatomical variability of mandibular neurovascular canals (mandibular, incisive and lingual canals) of 129 modern humans and great apes (Homo, Pan and Gorilla) were analyzed by linear measurements on CBCT images. The Kruskal-Wallis non-parametric test and Dunn’s all pairs for joint ranks were applied to compare the variability of mandibular canals among these groups. Human, Chimpanzee and Gorilla groups showed significant differences in the dimensions of the mandibular canal, mental foramen, incisive canal, lingual canal and anterior mandibular bone width. Bifid mandibular canals and anterior loops were the anatomical variations most frequently observed in the Gorilla. Humans had a larger mental foramen and a distinctive incisive canal. The latter could not be identified in the Gorilla group. The variability in the anatomy within mandibles of human and non-human primates, shows different forms in the neurovascular structures. In comparison to the mandible of great apes, the incisive canal is suggested to be a feature unique to the human mandible.
Keywords: mandibular canal; anatomical variability; mandible; neurovascularisation; great apes